Obtaining Differentiation Premiums in the Presence of Fee Regulation in the Residential Real Estate Appraisal Industry. Issue 5 (3rd September 2017) - Sanderford, Andrew R.; Read, Dustin C.; Xu, Weibin; Boyle, Kevin J.
Abstract: In the context of the customary and reasonable pricing standard imposed by the Dodd–Frank Act, this article considers whether residential real estate appraisers are able to obtain differentiation premiums for their services. Regression models estimated using data from the Commonwealth of Virginia offer some evidence that professional certifications and the complexity of an appraisal task are positively associated with fee levels in this type of regulatory environment. However, differentiation premiums appear more difficult to obtain across geographies and when an appraisal is procured by an appraisal management company. The findings suggest appraisers can differentiate themselves from competitors, but also that policymakers should be mindful of the potential for commodification on the residential appraisal industry in select market settings. Since appraisals are a critical component of the mortgage underwriting process, and the majority of housing transactions utilize mortgage debt, developing new understanding of how policies influence appraisers and how the appraisal process makes an important contribution to the housing policy literature.